Long-term effects of bouldering psychotherapy on depression: benefits can be maintained across a 12-month follow-up. Issue 12 (December 2019) - Schwarz, Laura; Dorscht, Lisa; Book, Stephanie; Stelzer, Eva-Maria; Kornhuber, Johannes; Luttenberger, Katharina
Abstract: Background: Previous studies have identified positive effects of Bouldering Psychotherapy (BPT) on symptoms of depression. The aim of the present study was to investigate the short- and long-term effects of BPT on 97 participants with depression. Methods: BPT took place once a week over a period of 8 weeks. In a waitlist control group design, participants were assessed at baseline and after 8 weeks (end of BPT for the intervention group; start of BPT for the waitlist group), 16 weeks, and 12 months. The main outcome was severity of depression measured with the Beck Depression Inventory II (BDI-II). Results: Depression scores dropped by 7.21 on the BDI-II during the first intervention period with a Cohen's d of 0.59. A regression analysis at t1 showed that group allocation ( p < .001) was the only significant predictor besides the baseline depression score ( p < .001). A 12-month (after t0) follow-up measurement showed that the decrease in depression severity remained stable during that time, with values of d = 0.37 for the intervention group and d = 0.43 for the waitlist group. Limitations: Limitations of the study are the assessment of symptoms via only self-report, the lack of a control group during follow-up, and different durations of the follow-up period in the two groups. Conclusion: Our results augment the findings of previous studies regarding the short-term effects of BPT and provide initial evidence that the positive effects of BPT on depression severity can be maintained across a period of 12 months. Abstract : Psychology; Psychiatry; Bouldering; Long-term effect; Exercise; Depression